Indonesian Capital Market Response to Tax Reforms: An Integrated Event Study Analysis with Methodological Robustness - Shella Febriyanti; Sri Setia Ningsih (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2026)
This study examines how Indonesia’s capital market responds to major tax reforms, which hold the potential to influence investor behavior through shifts in risk perception, growth expectations, and confidence in fiscal direction. Using an event study approach, the analysis evaluates market reactions to ten key tax policies through mean-adjusted and market model return estimations. The sample consists of 29 listed companies across multiple sectors, producing 290 Cumulative Abnormal Return (CAR) observations. The testing process includes abnormal return calculations, t-statistics, the proportion of positive reactions, and several robustness checks to validate consistency across different event windows. The findings indicate that average CAR values are generally close to zero, with most policy events showing limited statistical significance. Policies that enhance business certainty, such as the Job Creation Law and the Harmonization of Tax Regulations Law (HPP), tend to generate clearer positive reactions. In contrast, policies that raise tax burdens or are associated with the pandemic show negative or insignificant effects. Sectoral results reveal that energy and mining tend to be more stable compared to infrastructure. The study is limited by its sample size and short-term focus, suggesting the need for broader sector inclusion, volatility-based or machine learning approaches, and macroeconomic or sentiment variables in future research